Opportunities and Challenges in the Operations Management for Industry 4.0 - Peeyush Vats; Rekha Gupta; Divya Gupta (International Journal of Advanced Robotics and Automation Technology, 2025)
This study investigates the opportunities and challenges in the operations of composite manufacturing industry for the adoption of Industry 4.0. As known from the literature that industry-4.0 is referred as the fourth industrial revolution which majorly focuses on cyber-physical systems. It is suggested that the instantaneous integration of digital and physical systems, in conjunction with new transformative technologies that facilitate work, will revolutionise the ways of work and, as a result, there is process of work management. This customary trade-offs in operations between the aspiring objectives of quality, speed, flexibility, and cost have potential to be disrupted or, at the very least, altered by this technology, which has the capacity to disrupt them. The purpose of this article is to present an overview of the key transformative technologies of Industry-4.0 to find the opportunities and challenges in the operations of composite manufacturing industry for the adoption of Industry 4.0. Mainly composite manufacturing industries have been considered to execute this study. In this study, the opportunities and challenges have been explored while implementing Indutry-4.0 technologies via advanced robotics (AR), artificial intelligence (AI), blockchain technology (BCT), internet of things (IoT), additive manufacturing (AM) in operations of composite manufacturing industry.
Keywords: Additive manufacturing; Industry 4.0; artificial-intelligence; blockchain; composite; information technology; manufacturing; robots